Glutaminase C Regulates Microglial Activation and Pro-inflammatory Exosome Release: Relevance to the Pathogenesis of Alzheimer’s Disease - Gao, Ge; Zhao, Shu; Xia, Xiaohuan; Li, Chunhong; Li, Congcong; Ji, Chenhui; Sheng, Shiyang; Tang, Yalin; Zhu, Jie; Wang, Yi; Huang, Yunlong; Zheng, Jialin C. (Frontiers in Cellular Neuroscience, 2019)
Microglia activation is a key pathogenic process at the onset of Alzheimer’s disease (AD). Identifying regulators of microglia activation bears great potential in elucidating causes and mechanisms of AD and determining candidates for early intervention. Previous studies demonstrate abnormal elevation of glutaminase C (GAC) in HIV-infected or immune-activated microglia. However, whether GAC elevation causes microglia activation remains unknown. In this study, we found heightened expression levels of GAC in early AD mouse brain tissues compared with those in control littermates. Investigations on cell types involved revealed that GAC is increased in primary mouse microglia following pro-inflammatory stimulation. To model GAC elevation we overexpressed GAC by plasmid transfection and observed that GAC-overexpression shift the microglial phenotype to a pro-inflammatory state. Treatment with BPTES, a glutaminase inhibitor, reversed LPS-induced microglia activation and inflammation. Furthermore, we discovered that GAC overexpression in mouse microglia increased exosome release and changed exosome content, which includes specific packaging of pro-inflammatory miRNAs that activate microglia. Together, our results demonstrate a causal effect of GAC elevation on microglia activation and exosome release, which promote the establishment of pro-inflammatory environment. Therefore, GAC may serve as a promising candidate for early diagnosis and intervention of AD.